2014
DOI: 10.4172/2155-6199.1000238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Metal Uptake by E. coli and Bacillus sps

Abstract: Over the past century, unrestricted mining, extensive industrialization, modern agricultural practices and faulty waste disposal methods have resulted in the release of unprecedented levels of toxic heavy metals like Cd, Hg, Ag, Sn, Pb, Cu, Co, Mn, Zn, etc into the environment. Many metals are essential for microbial growth in less concentration, yet are toxic in higher concentrations. Biosorption is an attractive alternative approach which involves the binding or adsorption of heavy metals to living or dead c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…However, E. coli showed decreased cellular viability from the fourth amendment probably in response to platinum toxicity. This is not unusual as a previous study had shown a reduction in E. coli growth when treated with several toxic metals including Cu, Cd, Zn, and Hg (1-5 ppm) [26]. In this study, E. coli was found to be capable platinum biomineralization.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, E. coli showed decreased cellular viability from the fourth amendment probably in response to platinum toxicity. This is not unusual as a previous study had shown a reduction in E. coli growth when treated with several toxic metals including Cu, Cd, Zn, and Hg (1-5 ppm) [26]. In this study, E. coli was found to be capable platinum biomineralization.…”
Section: Discussionsupporting
confidence: 76%
“…Most E. coli strains have been shown to be sensitive to heavy metals such as Zn, Cd, and Hg; studies have also shown that exposure of E. coli to Pt complexes (e.g. (NH 4 ) 2 [PtCl 6 ]) results in the inhibition of cell division [25][26][27][28][29]. However, some E. coli strains have been shown to exhibit a range of tolerances to different concentrations of Zn(II), Cd(II), Co(II), Ni(II) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they cause damage on different levels of the organism. By translocation of the mercury ions through the cell membranes, the intracellular metal-binding sites are exposed (Gourdon et al 1990) that ultimately can result in death of sensitive organisms unless a means of detoxification is induced or already possessed (Vijayadeep and Sastry 2014). The damage is mostly due to the avidity of the mercuric ions for the sulfhydryl groups of proteins, which they block and inactivate and to high affinity for phosphate groups and active groups of ADP or ATP, and for replacement of Fe from some iron-sulfur clusters (Patra and Sharma 2000;Nabi 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many metals are essential for growth of microorganisms in lower concentrations, yet are toxic in higher concentrations. Many microorganisms have the ability to selectively accumulate metals by the process of biosorption which involves the building or adsorption of heavy metals to living or dead cells (Vijayadeep and Sastry, 2014). The concentrations of the heavy metals analysed in the petroleum sludge in this study may not have affected the microbial growth in the overall biodegradation process.…”
Section: Resultsmentioning
confidence: 89%